The Influence of Leadership and Organizational Culture Employee Performance at Medan Adventist Hospital - Pandiangan, Gibson; Malau, Harman; Siagian, Harlyn (International Journal of Business, Law, and Education, 2024)
The aim of this investigation was to ascertain whether leadership and organizational culture impact employee performance at Medan Adventist Hospital. This study adopts a quantitative research design, aimed at discerning and demonstrating the influence of one variable on others. The study encompasses the entire workforce of Medan Adventist Hospital, totaling 372 individuals. Employing the Solovin-based sampling technique, a total of seventy-nine employees will be selected for interviews, ensuring proportional representation across sections. The research employs descriptive data analysis techniques alongside multiple regression analysis, incorporating T-tests (partial tests), F-tests (simultaneous tests), and determination coefficient tests (R2). The analysis tool utilized in this study is the multiple linear regression model. The findings of this research validate that individual leadership significantly impacts the performance of Medan Adventist Hospital employees, while individual organizational culture similarly exerts a notable influence. Simultaneous testing demonstrates that both leadership and organizational culture collectively affect the performance of employees at Medan Adventist Hospital.